The reliability of the received information if it is registered in the single photon communication channel using the photon counter - A. M. Timofeev (Informatika)
When measuring low-power optical signals, the receiving modules of systems should ensure a sufficiently high accuracy of the received data. In this regard, it is advisable to use photon counters. They are highly sensitive, but are characterized by data recording errors. The aim of this work is to determine the influence of average pulse count rate of photons as the output of the counter on the fidelity of received information taking into account also the dead time of the counter. The formula is obtained for calculating the reliability of data received over an asynchronous binary asymmetric homogeneous communication channel without memory with erasure, when photon counter with a dead time of prolonging type was used as a receiving module. According to the results of mathematical modeling, it was established that with an increase in the average count rate of signal pulses at the output of the photon counter in symbols 1 (ns1), the reliability of the received data D grows up to saturation. Moreover, when other parameters being equal, with an increase of the average duration of the dead time of a prolonged type (τd), the saturation of the D(ns1) dependence is fixed for large values of the average counting rate of signal pulses. For example, with ns1 ≥ 35,0×104 s –1 for τd = 0; with ns1 ≥ 38,9×104 s –1 for τd = 5 µs; with ns1 ≥ 43,7×104 s –1 for τd = 10 µs; with ns1 ≥ 50,0×104 s –1 for τd = 15 µs.